Comparative efficacy of non-invasive brain stimulation for attention-deficit/hyperactivity disorder: a systematic review and network meta-analysis - Liang, Xinwen; Wei, Xiaoyu; Huang, Yan; Li, Jing; Feng, Huan; Fan, Jingyuan; Zhang, Longguo; Wang, Zhijiang; Zhao, Xin; Pan, Weimin; Liu, Rui (Frontiers in Neurology, 2025)
IntroductionIn recent years, non-invasive brain stimulation (NIBS) interventions for attention-deficit/hyperactivity disorder (ADHD) have received increasing attention. However, which of the various NIBS methods is more effective in improving cognitive functions and core symptoms in patients with ADHD remains unclear.MethodsRandomized controlled trials (RCTs) on NIBS in patients with ADHD were searched. Standardized mean differences (SMDs) for cognitive functions and core symptoms changes were pooled in Bayesian network meta-analyses.ResultAfter reviewing 3,976 retrieved citations, a total of 37 RCTs (N = 1,615 participants) were included. This NMA provides evidence that none of the NIBS interventions significantly improved inhibitory control compared to sham controls. However, a statistically significant difference was observed between anodal transcranial direct current stimulation (tDCS) over the left DLPFC plus cathodal tDCS over the right supraorbital area 1.5 mA (SMD = −0.87, 95% CI: −1.80 to −0.07) and High-definition anodal transcranial direct current stimulation over the vertex 0.25 mA (SMD = −1.04, 95% CI: −2.09 to 0.00). In terms of working memory, anodal tDCS over the left DLPFC plus cathodal tDCS over the right DLPFC (SMD = 0.95, 95% CI: 0.05–1.84) and anodal tDCS over the right inferior frontal cortex (rIFC) plus cathodal tDCS over the right supraorbital area (SMD = 0.86, 95% CI: 0.28–1.45) were associated with significant improvements compared to sham stimulation. For cognitive flexibility, only anodal tDCS over the left DLPFC plus cathodal tDCS over the right supraorbital area (SMD = −0.76, 95% CI: −1.31 to −0.21) demonstrated a statistically significant benefit relative to sham. Regarding inattention, both transcranial pulse stimulation (SMD = −2.62, 95% CI: −6.35 to 1.12) and transcranial alternating current stimulation 10 Hz (SMD = −2.35, 95% CI: −5.00 to 0.30) showed favorable trends in comparison with sham; however, these differences did not reach statistical significance, though they approached the threshold. Finally, no NIBS intervention was found to significantly improve hypersensitivity or impulsivity when compared to sham stimulation.ConclusionThe dual-tDCS and a-tDCS may be considered among the preferred NIBS interventions for improving cognitive function in ADHD. Specifically, anodal tDCS over the left DLPFC plus cathodal tDCS over the right supraorbital area improved cognitive flexibility; while anodal tDCS over the left DLPFC plus cathodal tDCS over the right DLPFC enhanced working memory; both dual-tDCS and a-tDCS demonstrated superior efficacy relative to repetitive transcranial magnetic stimulation (rTMS) for inhibitory control; further research is needed to investigate TPS for improving attention and impulsivity.